Effect of oral supplementation of palm oil tocotrienol-rich fraction on oocytes and reproductive organ of female rats / Mohd Fareez Faisal Saad@Asri - Saad@Asri, Mohd Fareez Faisal (2015)
Infertility is a biological inability of an individual to conceive and many cases are related to female infertility. Palm oil tocotrienol-rich fraction (TRF) was demonstrated to have a potential antioxidant to provide protection against adverse effect of oxidative stress related to female reproductive system. This was performed to investigate the effect of oral supplementation of palm oil TRF on oocyte and reproductive organ of female rat model. 30 mg/kg, 60 mg/kg and 90 mg/kg of palm oil TRF were prepared from Gold Tri.E™. Thirty (30) adult female Wistar albino rats were randomly divided into 5 groups (n=6). Control negative group was administered with distilled water (ad libitum, Gl), control positive group was administered orally with com oil (0.1 ml, G2) and treatment groups were administered orally with com oil and palm oil TRF at doses of 30 mg/kg, 60 mg/kg and 90 mg/kg (G3-G5). After seven consecutive days of treatment, blood collection was performed by using a guillotine with a sharp blade to cut neck close to the head for biochemical analysis. Oviducts were collected for oocyte analysis. Results of oocyte count and grading of cumulusoocyte- complexes (COCs) showed no significant different between treatment groups and control groups. Oocyte count was increased in rats treated with 60 mg/kg of palm oil TRF compared to other groups. Grading of COCs also showed increment of normal COCs in rat treated with 60 mg/kg of palm oil TRF. Assessment of hepatotoxicity and nephrotoxicity evaluated that hepatotoxicity and nephrotoxicity effects of high dose group (G5). Histopathological finding has revealed significantly increase of ovarian surface epithelium (OSE) height in high dose group (G5). This study suggested that lower and higher doses of oral supplementation of palm oil TRF may increase quality of oocyte and also may cause adverse effects on liver and kidney, respectively. Further studies should be carried out to explore precisely on the effect of different doses of oral supplementation of palm oil TRF especially in female reproductive system.